A Review on Nutritive and Medicinal Importance of Shigru (Moringa Oleifera Lam.). - Samiksha; Kumar, Mukesh; Meena, Narendra; Mishra, Rajesh Chandra (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda seeks to promote total health. Ayurveda prioritises maintaining health before treating diseases by reducing their symptoms. Additionally, it has been described as the science of age protection (ayu.). Diet, sleep, and brahmacharya(abstinence) are the three sub pillars of health . Aahar, in our opinion, is crucial for maintaining both a healthy body and mind. Shigru (Moringa oleifera) is an anti-oxidant herb. It guards against numerous infections and shields the body from free radicals. Shigru is a plant with a wide variety of therapeutic applications and great nutritional value. At various locations, the various portions of this plant are used as food. It is used to treat conditions like high blood pressure, diabetes, malnutrition, arthritis, and joint diseases. This article has reviewed and explained the different health advantages of using shigru as well as how to use it as Aahar.